2008
DOI: 10.1113/jphysiol.2007.149625
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in the involvement of pyruvate dehydrogenase complex in muscle lactate accumulation during lipopolysaccharide infusion in rats

Abstract: A characteristic manifestation of sepsis is muscle lactate accumulation. This study examined any putative (causative) association between pyruvate dehydrogenase complex (PDC) inhibition and lactate accumulation in the extensor digitorum longus (EDL) muscle of rats infused with lipopolysaccharide (LPS), and explored the involvement of increased transcription of muscle-specific pyruvate dehydrogenase kinase (PDK) isoenzymes. Conscious, male Sprague-Dawley rats were infused I.V. with saline (0.4 ml h −1 , control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 46 publications
6
47
1
1
Order By: Relevance
“…Furthermore, we have strongly implicated the dysregulation of AKT/FOXO signalling in these events [15]. The up-regulation of muscle PDK4 mRNA observed with Con/LPS treatment in the present study ( Figure 2H), along with the increase in muscle lactate accumulation (Figure 4), is entirely consistent with our previous observations [7,15]. Moreover, we have also reported that blunting the cytokine response to LPS using low-dose Dex offset the dysregulation of Akt signalling, and normalized muscle PDK4 mRNA and protein expression, PDC activity and lactate accumulation [16].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Furthermore, we have strongly implicated the dysregulation of AKT/FOXO signalling in these events [15]. The up-regulation of muscle PDK4 mRNA observed with Con/LPS treatment in the present study ( Figure 2H), along with the increase in muscle lactate accumulation (Figure 4), is entirely consistent with our previous observations [7,15]. Moreover, we have also reported that blunting the cytokine response to LPS using low-dose Dex offset the dysregulation of Akt signalling, and normalized muscle PDK4 mRNA and protein expression, PDC activity and lactate accumulation [16].…”
Section: Discussionsupporting
confidence: 82%
“…We have previously demonstrated a cytokine-linked increase in PDK4 mRNA and protein expression, coupled to the inhibition of PDC activity and stimulation of lactate accumulation in muscle during LPS-induced endotoxaemia in this rodent model [7,15]. Furthermore, we have strongly implicated the dysregulation of AKT/FOXO signalling in these events [15].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Rodent studies have demonstrated that sepsis causes a reduction in the activity and quantity of PDH, which has, in turn, been associated with increased levels of lactate (6)(7)(8). However, no study has measured PDH activity and quantity during sepsis in humans.…”
mentioning
confidence: 99%
“…In a physiological environment rich in oxygen but also in pathophysiological conditions (like diet rich in lipids, starvation or diabetes) the heart can utilize all metabolites but it prefers FFA oxidation, from which it gets 60-90% of the necessary energy, obtaining the remaining part from the oxidation of glucose and ketone bodies [39]. The myocardiocyte gets FFA mainly taking up tryglicerides (TG)-rich lipoproteins (LP) (chylomicrons and very low-density lipoprotein, VLDL) through the endothelial lipoprotein lipase (LPL), enzyme present in the capillary endothelium and bound to it through a proteoglycan, the Glycosylphosphatidyl-inositol high density lipoprotein-binding protein 1 (GPIHBP1), which anchors LPL to endothelium and serves as a bridge allowing LP uptake [40].…”
Section: Tg and Ffa Utilization In The Normal Heartmentioning
confidence: 99%